9, 9-Dimethyl-9, 10-dihydroacridine functionalized phosphoindole oxides with AIE property for OLED application. Issue 3 (2nd July 2020) - Li, Jianqing; Zhuang, Zeyan; Zhu, Xiangyu; Zhao, Zujin; Tang, Ben Zhong
Abstract : Aggregation-induced emission (AIE) has attracted widespread attention of late in academic and industrial circles owing to its diverse applications. Developing AIE-active materials for application in organic light-emitting diodes (OLEDs) has become an effective method of improving device efficiency and stability. In this work, two novel luminogens (PIO- α -DMAc and PIO- β -DMAc) consisting of 9, 9-dimethyl-9, 10-dihydroacridine and phosphoindole oxide were synthesized and systemically characterized. Their crystal structures, thermal stabilities, electronic structures, and electrochemical behaviors were studied. They showed apparent AIE properties and emitted strongly in the aggregated state. Non-doped and doped green OLEDs were fabricated using these luminogens as light-emitting layers, and exhibited high brightness, good electroluminescence efficiencies, and low turn-on voltages.